The Effectiveness of Flipped Classroom in Improving Motivation and Achievement among Slow Learners in Mathematics - Al-Zboun, Ahmed Ali (Dirasat: Educational Sciences, 2020)
The purpose of this study was to investigate the effectiveness of flipped classroom in improving motivation and achievement among slow learners in mathematics. The researcher developed a mathematics test and scale of motivation. The study sample consists of (30) slow learners. They were divided into two groups: an experimental and a control group. The findings of the study showed that there are statistically significant differences at the level of (α =0.05) between the means of both groups performance in improving motivation and achievement among slow learners in mathematics as a whole in the post test attributed to the teaching strategy in favor of the experimental group. The results also showed a positive correlation between the level of motivation and achievement in mathematics. The study recommended applying the strategy of flipped classroom to improve motivation and achievement among slow learners in mathematics.